PENGEMBANGAN DESAIN POMPA LISTRIK SENTRIFUGAL UNTUK GALLON AIR MINUM - Muhamad Imron Zamzani; Indro Prakoso (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
The gallon water pump used to meet household needs, in general, is a manual pump, with an affordable price, this pump is excellent. However, the use of manual pumps is considered ineffective for water intake in gallons, so development innovation is needed for a more effective design. The purpose of this research is to design a centrifugal electric pump that is designed to facilitate the collection of water in gallons on a scale of household needs. The researcher used the Kano method to design the pump, this method was chosen so that user satisfaction is guaranteed. To get the level of product satisfaction, by distributing questionnaires to 44 respondents with 10 attributes. Analysis to determine the level of satisfaction of centrifugal electric pump products using the End-User Computing Satisfaction (EUCS) method. The level of satisfaction of centrifugal electric pump products designed with the Kano method states that most of the attributes are in an Attractive condition, meaning that the customer wants the centrifugal electric pump product to be produced immediately. With the proposed design based on human anthropometry, it is expected to be able to increase customer satisfaction.